가스터빈 기동장치 센서리스 속도제어로직 성능실험 - 류호선(Hoseon Ryu); 문주영(jooyoung Moon); 이의택(Uitaek Lee); 이주현(Joohyun Lee); 강윤모(Yunmo Kang); 박만기(Manki Park) (전기학회 논문지 P권, 66(2), 2017)
The gas turbine static starter rotates the stationary synchronous machine by the interaction of the rotor and the stator. The detection from the initial position of the rotor has been an important issue to drive with optimum torque. Previously, the gas turbine starter was used by attaching the encoder to the synchronous machine, but the position and velocity of the rotor have been estimated by sensor-less method until recently due to the difficulty in attaching and detaching and damage caused by the shaft voltage noise. In this paper, Rotor initial(stationary state) position estimation, forced commutation control(speed less than 10%), and natural commutation control(speed more than 10%) method using magnetic flux with integrated terminal voltage were presented and the sensor-less speed control performance was verified. As a result of making and evaluating the 29 kVA synchronous machine and the starting device, the performance of each control mode was satisfactory. Furthermore, the applied technology is expected to be used for the development of the gas turbine starter of tens of MW class and the field application.